(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background:Soft contact lenses are widely used for vision correction due to their comfort and optical performance. The manufacturing technique—whether lathe-cut or cast-molded—can significantly affect lens properties, including surface smoothness, hydration, and oxygen transmissibility. These factors may influence ocular surface health and long-term wearability. Objective: To compare the impact of lathe-cut versus cast-molding soft contact lens manufacturing techniques on ocular surface integrity among first-time lens users. Methods: This double-blind randomized control trial included 70 healthy participants aged 15–35 years with no prior history of contact lens wear, ocular disease, or systemic conditions affecting the eye. This study was conducted in Eye 2 Eye Optometrists, Lahore and ophthalmology department Fuji Foundation hospital Lahore. Participants were randomly assigned to receive either lathe-cut or cast-molded soft contact lenses. Baseline assessments included visual acuity, refractive error, corneal curvature, tear film breakup time (TBUT), Schirmer’s test, and Ocular Surface Disease Index (OSDI) scores. Follow-up evaluations were conducted at 3 and 6 months. Statistical analysis was performed using Chi-square tests and paired t-tests; significance was set at p<0.05. Results:Among the 70 participants, 27 (38.6%) were male and 43 (61.4%) were female. While both groups showed significant intra-group improvements in TBUT and Schirmer scores over the 6-month period (p=0.001), cast-molded lenses demonstrated a more consistent improvement in tear film stability and tear production. Normal OSDI scores were observed in 62.9% of the lathe-cut group and 51.4% of the cast-molded group; however, this difference was not statistically significant (p=0.334). Conclusion:Both lathe-cut and cast-molded soft contact lenses are effective in maintaining ocular surface integrity and improving tear film stability in first-time users. While lathe-cut lenses showed slightly higher rates of subjective comfort, cast-molded lenses provided more consistent improvements in objective tear metrics. These findings support the continued clinical relevance of both manufacturing techniques, with a need for patient-specific material and design selection to optimize outcomes.